2009
DOI: 10.1002/jcop.20337
|View full text |Cite
|
Sign up to set email alerts
|

Resilience factors in families living with people with mental illnesses

Abstract: In South Africa, a substantial burden is placed on families living with people with mental illnesses. The aim of this study was to identify resilience factors in families living in an underprivileged area, caring for people with mental illnesses. Data was obtained from family representatives (N 5 34) using semistructured interviews and a set of seven self-report, quantitative questionnaires during the course of a onceoff interview. The results of the qualitative analysis show that the most commonly cited resil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 12 publications
7
41
1
10
Order By: Relevance
“…However, no significant correlation was found in the quantitative results between family adaptation and the family's tendency to use spiritual and religious support as a coping strategy (see Table 1). Similar discrepancies have been found in other family resilience studies (Greeff & Thiel, 2012;Greeff et al, 2006;Jonker & Greeff, 2009). These contrasting results could possibly be attributed to the nature of the items in the measuring instrument (F-COPES: Spiritual support), as the items focus on the families' involvement in a religious or congregational affiliation and neglect the spiritual support provided through personal or familial rituals (e.g., prayer, meditation, family Bible study).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, no significant correlation was found in the quantitative results between family adaptation and the family's tendency to use spiritual and religious support as a coping strategy (see Table 1). Similar discrepancies have been found in other family resilience studies (Greeff & Thiel, 2012;Greeff et al, 2006;Jonker & Greeff, 2009). These contrasting results could possibly be attributed to the nature of the items in the measuring instrument (F-COPES: Spiritual support), as the items focus on the families' involvement in a religious or congregational affiliation and neglect the spiritual support provided through personal or familial rituals (e.g., prayer, meditation, family Bible study).…”
Section: Discussionsupporting
confidence: 80%
“…The theoretical framework in the current study also identified cohesiveness among family members as a significant resilience resource (Patterson, 2002;Walsh, 2003). Jonker and Greeff's (2009) qualitative results also identified family connectedness as a resilience resource.…”
Section: Family Resilience In Caring For Dementiamentioning
confidence: 65%
See 2 more Smart Citations
“…This research mainly focuses on mental health [25,26], family relations [27,28], children and young people [29,30], and aging [31,32]. These studies have shown that faith plays a positive role in resilience building: utilising faith for meaning-making and framing of events contributed to the enhanced ability of individuals to deal with major negative life situations.…”
Section: Faith Resilience In Everyday Lifementioning
confidence: 99%